The Governance of the SEA in the 2007-2013 EU Programs: the case of Italy - Roberto Del Ciello; Andrea Forni; Federica Scipioni; Antonio Disi; Anna Salama (European Regional Science Association (ERSA), 2011)
The Governance of the SEA in the 2007-2013 EU Programs: the case of Italy The European Union 2007-2013 funds programming is a relevant frame in order to analyse the implementation of Strategic Environment Assessment (SEA) of plans and programs. In this paper the SEAs of 21 Regional Development Programs and 21 Rural Development Plans, implemented by the Italian regions, between the second half of 2006 and the end of 2007, have been reviewed. According to the SEA literature the study is mainly focused on the process than on the procedure, so that some aspects (i.e. the transposition of the SEA Directive into national law) are not tackled in depth. On the other end the attention to the processes, allows to analyse the different approaches and strategies the Regions followed through to assess the same category of program, in the same period, with the same framework of rules. The complexity of the processes and the huge documentation to be examined, in addition to the wide range of approaches experienced by the regions, required to focus the study on the following interpretative keys: - the instruments of governance arranged by the regions in order to manage the contextual processes of programming and assessment; - the definition of the objectives and the targets and the capacity to systematize coherently the indicators used in the context definition, within the assessment and monitoring; - the participation, as regards the adopted modality and the real effectiveness of this phase of the process in order to drive the assessment and therefore the program; - finally a privileged, even if not comprehensive, reading of the coherence of the measures in the energy field included in the operative programs with the regional sectorial programming. The quantitative and qualitative results of the paper represent a useful baseline to evaluate the present intermediate phase of the EC co-financed Operative Programs implementation and to compare the Italian regions case with other Member States experiences.
Keywords: 330